ANALISIS PERBANDINGAN PROGRAM KBANTUAN LANGSUNG TUNAI (BLT) DENGAN PROGRAM KELUARGA HARAPAN (PKH) DALAM MENSEJAHTERAKAN MASYARAKAT DI RW 001 KECAMATAN JATISAMPURNA - Yusrita Florentin (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The Family Hope Program is a social protection program that provides cash assistance to poor households (RTM) and for RTM family members are required to carry out the terms and conditions that have been set. Direct Cash Assistance is assistance provided by the government to the community in the form of cash to help them face economic difficulties. The purpose of this study is to find out 1) the comparison of the Direct Cash Assistance Program (BLT) and the Family Hope Program (PKH), 2) What are the supporting and inhibiting factors in increasing the Cash Direct Assistance Program (BLT) and the Family Hope Program (PKH). In this study used a qualitative approach. Data collection techniques in this study are the methods of observation, interviews and documentation. Data analysis is done inductively